Characteristics of ear fullness and synaptic loss in ear fullness revealed by SV2A positron emission tomographycortical - Zhou, En; Xiao, Xuping; Liu, Bin; Tan, Zhiqiang; Zhong, JiaYu (Frontiers in Molecular Neuroscience, 2024)
ObjectiveStudies on feeling of ear fullness (FEF) related to sudden sensorineural hearing loss(SSNHL) are limited. The mechanisms of FEF are unclear. This study aimed to explore the characteristics and related brain activation of SSNHL with FEF.MethodsA total of 269 SSNHL patients were prospectively observed and divided into two groups, with FEF and without FEF. Fifteen SSNHL patients with FEF and 20 healthy controls (HCs) were recruited and underwent 18F-SynVesT-1 static PET. Standardized uptake values ratios (SUVr) of 18F-SynVesT-1 were computed between regions of interest.ResultsThe occurrence of FEF was not related to the audiogram type or severity of hearing loss. There was a positive correlation between the degree of FEF and the degree of hearing loss. Recovery from FEF was not related to the audiogram shape, the degree of hearing loss or recovery. Fifteen SSNHL patients with FEF had relatively low 18F-SynVesT-1 uptake in the right middle frontal gyrus, right inferior frontal gyrus, right middle temporal gyrus, bilateral parietal lobe sub-gyral and left medial frontal gyrus, as compared with HCs. There was no relatively high 18F-SynVesT-1 uptake in the cerebral cortex.ConclusionThe occurrence and recovery of FEF in SSNHL patients are not related to the classification, degree and recovery of hearing loss. The 18F-SynVesT-1 uptake in the cerebral cortex of patients experiencing SSNHL and FEF has shown alterations. This indicates that FEF may be related to cortical reorganization after the sudden impairment of unilateral auditory input.